Preparing cedrene from ethylene-vinyl acetate copolymer and polyethylene terephthalate of waste solar cells. (1st May 2020) - Qin, Baojia; Lin, Mi; Huang, Zhe; Qiu, Ruijun; Ruan, Jujun; Tang, Yetao; Qiu, Rongliang
Abstract: Quantities of waste solar cells have been produced due to their widespread sustainable energy applications. Due to the complicated composition of waste solar cells, the disposal of waste solar cells has been the hot spot of sustainable development and environmental protection research. To our knowledge, little information has been reported about the disposal of waste solar cells. For the safe disposal of waste solar cells, and to produce economic benefits, the present study applied the density functional theory to design the transformation pathways of organics in waste solar cells. The ethylene-vinyl acetate copolymer and polyethylene terephthalate of waste solar cells were transformed to 3, 6, 8, 8-tetramethyl-2, 3, 4, 7, 8, 8a-hexahydro-1H-3a, 7-methanoazulene (cedrene). It is the precursor of precious wound-healing medicine. The transformation pathways exhibited a total energy barrier of 58.79 kcal/mol, and thermodynamic calculations indicated the temperature required for breaking this energy barrier was 777.50 K. 3, 6, 8, 8-Tetramethyl-2, 3, 4, 7, 8, 8a-hexahydro-1H-3a, 7-methanoazulene was produced by vacuum heating at a temperature of 778.15 K, and the material had the most substantial proportion that accounted for 19.85 wt% in the products of vacuum heating. This paper provides insight into preparing the raw materials of medicine from the nonmetallic material of waste solar cells. Graphical abstract: Image 1